TEACHERS’ COMPREHENSIONS, PERCEPTIONS, AND ATTITUDES TOWARDS INCLUSIVE EDUCATION - Ruwandi Ruwandi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2012)
This study aims at finding out 1) the comprehensions of IslamicElementary School Teachers (MI) in Salatiga to inclusive education; 2) their perceptions; and 3) their attitudes to the inclusive education. This is a survey research. The primary data collection method used in this research was questionnaires, besides structural interviews. Based upon the calculation of the questionnaires, the writer found out that 1) the teachers’ comprehension to inclusive education is still low (88.1 %) and only 4.7 % feels having a little knowledge about it. In addition, 50.02 % have negative perceptions, and are only 21.46 % who have positive perceptions to it. Even though, 43.89 % have positive attitudes and 37.81 have negative attitudes to the inclusive education.